We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
-1
109
1
avatar+397 

deleted.

 Jun 9, 2019
edited by sinclairdragon428  Nov 20, 2019
 #1
avatar+104963 
+1

x(2x - 7) = 3  simplify

 

2x^2 - 7x - 3  = 0

 

2 ( x^2 - (7/2)x - 3/2)  = 0     divide through by 2

 

x^2 - (7/2)x - 3/2   = 0      complete the square on x

 

x^2 - (7/2)x  = 3/2

 

x^2 - (7/2)x  + 49/16   =  3/2 + 49/16

 

(x - 7/4)^2  =  (24 + 49) / 16

 

( x - 7/4)^2 = ( 73) / 16           take both roots

 

x - 7/4  =  ±√(73) / 4

 

x =   [ 7 ±√(73)  ] / 4

 

m = 7   n = 73   and p =4

 

So    m + n + p  =   84

 

 

cool cool cool

 Jun 9, 2019

20 Online Users